Confirmation of a theory: reconstruction of an alluvial plain development in a flume experiment - Bertalan, Lászió; Tóth, Csaba Albert; Szabó, Gergely; Kuda, František; Szabó, Szilárd (ERDKUNDE, 2016)
Fluvial geomorphologists have tried to describe the outstanding tectonically affected avulsion process of Tisza River at the Great Hungarian Plain by various theoretical concepts. Flume experiments provide the ability to examine the main characteristic processes of a highlighted surface development theory under controlled settings within an accelerated time scale. Our goal was to reconstruct and refine these hypotheses from a new experimental point of view. Contrary to the previous flume studies focused on a highlighted mechanism, our experiment combined several processes for confirmation purposes. In this study we performed an experiment of the avulsion process mentioned above on a 12 x 5 x 2.5 m flume where a special instrument was planted under the sand layers in order to simulate the vertical tectonic movements. A terrestrial laser scanner was used to record the different stages of the topographic evolution. We shaped the initial surface and executed the main landscape forming processes according to theoretical descriptions then with modifications to examine the similarities and differences between the experimental outcomes and the theoretical evolution. The results of three different types of scenarios proved the key role of the uplifting Nyírség alluvial fan in the channel direction changing process of Tisza River. On the other hand, the role of Bodrogköz area had been questioned. Flume experiments with appropriate equipment can serve as a suitable tool for the reconstruction of surface development theories taking into account several landscape forming processes simultaneously.